Assessing the Efficacy of Sneha Pottanam (Bundle Application) in Managing Vatha Related Diseases in Children - T. Priyanka; D. Muthu Krishnan; S. Simal; C. Shanmuga Priya; A. Satheesh Kumar (International Journal of Ayurveda and Pharma Research, 2024)
The Siddha system of medicine offers a holistic approach that addresses not only physical ailments but also the spiritual well-being of individuals. It classifies 4,448 types of diseases and categorizes treatments into two types: internal and external medicines. Pottanam is one of the treatment methods described by Siddhar Therayar in his text ‘Therayar Tharu’. Managing special needs children has become a significant challenge today. Sneha Pottanam, an external therapy mentioned in ‘Pillaipini Vagadam - Part 2’, is particularly used for managing Vatha-related disorders in pediatric cases. Aim & Objective: The aim of this review is to elaborate the efficacy of Pottanam (bundle application) and to evaluate the therapeutic efficacy of Sneha Pottanam, as described in ‘Pillaipini Vagadam – Part 2’, for the management of Vatha-related diseases through a comprehensive literature review. Materials & Methods: The review was conducted through Siddha literature, including ‘Pillaipini Vagadam – Part 2’, ‘Gunapadam’, ‘Pathartha Gunachinthamani’, the ‘Manual of Siddha External Therapy’, as well as research articles from Google Scholar and PubMed. Discussion: Siddha literature describes a wide range of external therapies, with Pottanam being a simple yet effective treatment for managing spasticity in Vatha-related diseases and balancing the three humors. This therapy rejuvenates the body and stimulates nerve endings. The ingredients in Sneha Pottanam act intradermally, making it an excellent remedy for special needs children by enhancing the function of motor and sensory receptors. Conclusion: The pharmacological properties and phytocomponents of Sneha Pottanam are highly effective in managing spasticity in special children and balancing the elevated Vatha humor. This review supports further studies on the ingredients of Sneha Pottanam, which could aid in the management of neurological disorders caused by imbalances in the body’s three humors.